2018
DOI: 10.1002/adfm.201800339
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer Coupling Induced Infrared Response in WS2/MoS2 Heterostructures Enhanced by Surface Plasmon Resonance

Abstract: Infrared light detection is generally limited by the intrinsic bandgap of semiconductors, which suppresses the freedom in infrared light photodetector design and hinders the development of high‐performance infrared light photodetector. In this work, for the first time infrared light (1030 nm) photodetectors are fabricated based on WS2/MoS2 heterostructures. Individual WS2 and MoS2 have no response to infrared light. The origin of infrared light response for WS2/MoS2 comes from the strong interlayer coupling wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
116
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 120 publications
(119 citation statements)
references
References 46 publications
1
116
0
Order By: Relevance
“…d) Photoresponse of a WS 2 /MoS 2 heterostructure induced by the interlayer coupling and surface plasmon resonance. Reproduced with permission . Copyright 2018, Wiley‐VCH.…”
Section: Hybrid Heterostructures Based On 2d Metal Chalcogenides For mentioning
confidence: 99%
See 1 more Smart Citation
“…d) Photoresponse of a WS 2 /MoS 2 heterostructure induced by the interlayer coupling and surface plasmon resonance. Reproduced with permission . Copyright 2018, Wiley‐VCH.…”
Section: Hybrid Heterostructures Based On 2d Metal Chalcogenides For mentioning
confidence: 99%
“…As a consequence, the IR photoresponse is attributed to the interlayer transition from the maximum valence of MoTe 2 to the minimum conduction band of MoS 2 . Very recently, our group fabricated a vertical heterostructure consisting of few layers WS 2 and MoS 2 , and systematically studied its optoelectronic properties at IR region (1030 nm), which originated from the strong coupling of interlayer which shrunk energy interval in the heterostructures . The responsivity of the heterostructures is limited to 8 mA W −1 , stemming from the reason that the few layers WS 2 and MoS 2 are indirect bandgap with low light absorption, and the response properties have been further enhanced utilizing SPR technique (Figure d) …”
Section: Hybrid Heterostructures Based On 2d Metal Chalcogenides For mentioning
confidence: 99%
“…In addition to mechanically exfoliated nanosheets, materials prepared with chemical vapor deposition (CVD) can also be manually stacked . Many heterostructures have been produced, such as MoS 2 /WS 2 , graphene/MoS 2 , MoSe 2 /graphene, and MoS 2 /WSe 2 , for flexible IR photodetectors and image sensor arrays.…”
Section: Production Of 2dhsmentioning
confidence: 99%
“…In recent years, SPR effect‐modified photodetectors have attracted many interest for their enhanced light absorption and detection sensitivity . Wu et al designed 2D + 0D photodetectors based on Ag shell‐isolated nanoparticles (SHIN)‐decorated MoS 2 .…”
Section: Two‐dimensional Heterostructuresmentioning
confidence: 99%
“…Very recently, Wu et al demonstrated a 16.2 nm MoS 2 phototransistor with a extended detection wavelength to 1550 nm . According to the reported features, MoS 2 always incorporates with other TMDs to form a Schottky Junction to realize high performance devices …”
Section: Introductionmentioning
confidence: 99%